Self-assembled metastable γ-Ga2O3 nanoflowers with hexagonal nanopetals for solar-blind photodetection - Teng, Yue (Advanced materials (Deerfield Beach, Fla.), 2014)
© 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.